Basic Training in Chemistry - Hoenig, Steven L. (Springer US, 2002)
Basic Training in Chemistry is unique in that it gathers into one source the essential information that is usually widely dispersed. This book can be used as a quick reference guide to the different disciplines of Chemistry: the areas covered are General, Inorganic, Organic, and Instrumental Analysis. Although comprehensive in nature, Basic Training in Chemistry is not meant to replace any standard textbook but rather to be a supplement or additional source of information, or even a comprehensive review guide. Basic Training in Chemistry is a useful addition to any academic or commercial laboratory setting where access to a wide variety of information is needed. The book can be an exceptional source of information for the undergraduate or graduate student as well as for the experienced chemist. Anyone needing a single source of information covering several different disciplines will find this book to be an excellent addition to their usual references.